FAKTOR-FAKTOR YANG MEMENGARUHI PENGHINDARAN PAJAK - MELVIN ALIFIANZA MARTIN; EDDY JONI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This research aims to obtain empirical evidence on the factors that influence tax avoidance. The factors tested consisting of financial distress, institutional ownership, independent commissioner, audit committee, profitability, and firm size. The company used in this research are manufacturing companies that listed on the Indonesia Stock Exchange (IDX) from 2017-2019 consistently. The number of research samples are 209 research data that obtained with purposive sampling method. This research uses a multiple regression analysis for hypothesis testing.This research results an empirical evidence. The evidence shows that financial distress, institutional ownership, independent commissioner, audit committee, profitability, and firm size have no effect on tax avoidance